The effects of livestock grazing on physicochemical properties and bacterial communities of perlite-rich soil - Premsuriya, Jiraphan; Leerach, Nontaphat; Laosena, Phatcharin; Hinthong, Woranich (PeerJ, 2024)
Livestock grazing has been proposed as a cost-effective way to reclaim post-mining lands. It can enhance soil fertility and biodiversity, but its impacts on soil quality and microbial communities vary across soil types. Moreover, waste from grazing raises concerns about pathogens that could pose risks to animal and human health. This study investigated the effects of grazing on post-mining perlite-rich soil in central Thailand. A comparative analysis of soil physicochemical properties and bacterial diversity was conducted between grazed and ungrazed sites. Bacterial diversity was assessed using 16S amplicon sequencing. The perlite-rich soil was found to be sandy, acidic, and to have low nutritional content. Grazing significantly improved the soil texture and nutrient content, suggesting its potential as a cost-effective reclamation strategy. The 16S metagenomic sequencing analysis revealed that microbial communities were impacted by livestock grazing. Specifically, shifts in the dominant bacterial phyla were identified, with increases in Firmicutes and Chloroflexi and a decrease in Actinobacteria. Concerns about increased levels of pathogenic Enterobacteriaceae due to grazing were not substantiated in perlite-rich soil. These bacteria were consistently found at low levels in all soil samples, regardless of livestock grazing. This study also identified a diverse population of Streptomycetaceae, including previously uncharacterized strains/species. This finding could be valuable given that this bacterial family is known for producing antibiotics and other secondary metabolites. However, grazing adversely impacted the abundance and diversity of Streptomycetaceae in this specific soil type. In line with previous research, this study demonstrated that the response of soil microbial communities to grazing varies significantly depending on the soil type, with unique responses appearing to be associated with perlite-rich soil. This emphasizes the importance of soil-specific research in understanding how grazing affects microbial communities. Future research should focus on optimizing grazing practices for perlite-rich soil and characterizing the Streptomycetaceae community for potential antibiotic and secondary metabolite discovery. The obtained findings should ultimately contribute to sustainable post-mining reclamation through livestock grazing and the preservation of valuable microbial resources.
Keywords: Soil metagenomic; Soil physicochemistry; Perlite; Livestock grazing; 16 rRNA gene sequencing